(untitled) (Eurasian Journal of Philology Science and Education, 2016)
The article deals with the means of linguistic expression of aggression in the media assessment of Russia and Kazakhstan. The fact that a frequency is an expression of negative evaluation, that in addition to objective reasons, is due to certain laws of human thinking «positive» or «good» for us is a kind of norm, ie a matter of course, while the phenomena.. violates the rules, concentrated on attention and are most relevant to refer to the speech and evaluation. Also under consideration is that the situation in modern Russia and Kazakhstan gives journalists especially a lot of reasons to use a rich palette of the lexical and grammatical means of negative evaluation, which has the Russian language. As a result, comparing the results of the semantic analysis means of linguistic expression of aggression in the media assessment of Kazakhstan and Russia.